Evaluation and comparison of laser surgery and surgical blade in the treatment of epulis fissuratum - Mahmood Hashemi H (Tehran University of Medical Sciences, 2005)
Background and Aim: The treatment of epulis fissuratum is surgery, but a new proposed modality is laser surgery. The aim of this study was the comparison between laser and blade surgery in the treatment of epulis fissuratum. Materials and Methods: In this clinical trial, 12 patients with epulis fissuratum were selected. The lesions were divided into two parts. One part was resected by laser and the other by surgical blade randomly and single blinded. The time of surgery, bleeding, wound repairment as well as the depth of vestibule were measured. Data were analyzed using Wilcoxon sign test and Paired t test with P<0.05 as the limit of significance. Results: The wound of laser surgery healed sooner and the depth of vestibule in laser side was deeper comparing with blade surgery. Also the time of surgery was less than blade. Conclusion: Based on the results of this study, we suggest that laser surgery is a more useful technique for the treatment of epulis fissuratum.